Internetworking troubleshooting handbook: A essential reference to solving difficults networking problems - H Kim Lew ...[et al.] (MacMillan, 1999)
The book provides the informationnecessary to troubleshoot many problems commonly encoutered in internetworks using Cisco hardware and software products